Multi‐objective fitting of concentration‐discharge relationships. Issue 11 (23rd November 2021) - Tunqui Neira, José Manuel; Andréassian, Vazken; Tallec, Gaëlle; Mouchel, Jean‐Marie
Abstract: Concentration–discharge ( C – Q ) relationships are widely used to assess the link between hydrological and biogeochemical processes at the catchment scale. C – Q relationships are mainly calibrated using mono‐objective methods to represent, either concentrations or discharge‐weighted concentrations (i.e., load). Based on its wide use in hydrological modelling, we test a multi‐objective calibration for the C – Q relationship parameters, using both concentration and load, and compare it to a mono‐objective calibration applied on either concentrations or load. This work is carried out on a high‐frequency dataset (ORACLE‐Orgeval Observatory, France). Our findings show that the multi‐objective calibration yield a better representation of C – Q relationships parameters during the high and low‐flow events. The multi‐objective calibration can be used for all forms of C – Q relationships and avoids issues of under‐representation of dilution processes characterized by high‐discharge, low‐concentration periods.